1992
DOI: 10.1007/bf00192255
|View full text |Cite
|
Sign up to set email alerts
|

Yearly chest radiography in the early detection of lung cancer following laryngeal cancer

Abstract: In a retrospective study of 556 patients (505 men, 51 women) with laryngeal cancer the incidence and prognosis of lung malignancies was studied in patients who were examined yearly by chest radiography. In 69 patients (12.4%) a lung malignancy was diagnosed, with 28 having a histologically confirmed second primary malignancy. All of these 69 patients were men. The incidence of radiologically detected lung malignancies, both second primary and metastatic cancer, is higher and more prolonged following supraglott… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

1994
1994
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 24 publications
1
22
0
Order By: Relevance
“…[7][8][9][10][11][12][13][14][15][16][17][18] There is a wide variation in the strategies for the specific sites. 6,[19][20][21][22][23][24][25][26] There is no evidence to suggest that any follow-up strategy is more efficient in detecting recurrences or improving the quality of life.…”
Section: Frequency Of Visitsmentioning
confidence: 99%
“…[7][8][9][10][11][12][13][14][15][16][17][18] There is a wide variation in the strategies for the specific sites. 6,[19][20][21][22][23][24][25][26] There is no evidence to suggest that any follow-up strategy is more efficient in detecting recurrences or improving the quality of life.…”
Section: Frequency Of Visitsmentioning
confidence: 99%
“…This increased sensitivity of CT scanning may be of benefit in the long-term follow-up of these patients, although it is worth noting that previous studies have shown no benefit to be gained from using chest x-ray of bronchoscopy in the follow-up of head and neck cancer patients. 14,15 At present, we advocate 1-monthly follow-up for the first year, 2-monthly for the second year, 3-monthly for the third year, and 6-monthly for the following 2 years. The aim of this follow-up is the detection of treatable recurrent disease and the identification of second primary tumors.…”
Section: Discussionmentioning
confidence: 96%
“…One reason is that chest radiography and sputum cytology are not done as frequently as recommended in many cases. Engelen et al 14 reported that the benefit of yearly chest radiography following laryngeal cancer in the early detection of lung cancer was low or even nil. But Amemiya et al 15 recommended the following examinations in the postoperative course of cancer to detect lung cancer de novo: (1) biannual chest radiography (posteroanterior and lateral view) for 5 years after operation and once a year after that; (2) annual sputum cytology, by collecting sputa for 3 days; and (3) annual fiberoptic bronchoscopy (only for laryngeal and pharyngeal cancer patients).…”
Section: Discussionmentioning
confidence: 98%